2008
DOI: 10.1143/jjap.47.7026
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Properties of Tensile-Strained GaAsP/GaInP Single Quantum Wells Grown By Metal Organic Chemical Vapor Deposition

Abstract: Tensile-strained GaAsP/GaInP single quantum well (QW) laser diode (LD) structures have been grown by low-pressure metal organic chemical vapor deposition (LP-MOCVD) and related photoluminescence (PL) properties have been investigated in detail. The samples have the same well thickness of 16 nm but different P compositions in a GaAsP QW. Two peaks in roomtemperature (RT) PL spectra are observed for samples with a P composition larger than 0.10. Temperature-and excitationpower-dependent PL spectra have been meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The thermodynamic equilibrium calculation is performed by HSC Chemistry 40 with Gibbs energy minimization method. The input parameters are the initial Ga, AsH 3 , PH 3 and H 2 gas phase amount, growth temperature, reactor pressure and a GaAs 1-y P y alloying interaction parameter (990 cal/mol). 9,16 The calculation therefore considered the formation of Ga, As hydrides (AsH 3 , AsH 2 , AsH), P hydrides (PH 3 , PH 2 , PH), As 2 , As 4 , P 2 , P 4 , AsP, As 2 P 2 , As 3 P, AsP 3 in the vapor phase, and GaAs 1-y P y alloy in the solid phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The thermodynamic equilibrium calculation is performed by HSC Chemistry 40 with Gibbs energy minimization method. The input parameters are the initial Ga, AsH 3 , PH 3 and H 2 gas phase amount, growth temperature, reactor pressure and a GaAs 1-y P y alloying interaction parameter (990 cal/mol). 9,16 The calculation therefore considered the formation of Ga, As hydrides (AsH 3 , AsH 2 , AsH), P hydrides (PH 3 , PH 2 , PH), As 2 , As 4 , P 2 , P 4 , AsP, As 2 P 2 , As 3 P, AsP 3 in the vapor phase, and GaAs 1-y P y alloy in the solid phase.…”
Section: Discussionmentioning
confidence: 99%
“…It assumes that the thermodynamic equilibrium is reached and the mass of each element is conserved. Since AsH 3 and PH 3 have positive free energies of formation, they appear in negligible amounts at equilibrium. The calculation output is the final amount of all species at thermodynamic equilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GaAsP quantum well structures have been grown by means of MOVPE and the strain-induced piezoelectric field has been studied and it is found that it can be adjusted by the energy band offset [4]. The optical properties of tensile-strained GaAsP/GaInP square quantum wells grown by MOCVD have been investigated with various characteristics of the PL spectra [5].…”
Section: Introductionmentioning
confidence: 99%